Peranan Pelajaran Sejarah Dalam Pengembangan Karakter Siswa Melalui Pembelajaran Berbasis Nilai Sejarah Lokal di SMA Negeri 65 Jakarta Barat - Jumardi Jumardi (Program Studi Pendidikan Sejarah Pascasarjana UNJ, 2017)
History is a subject that is closely related to the development of the nation's character aswell as the fostering of nationalism, the spirit of nationalism, the love of the homeland, the democraticspirit, and patriotism and learners can understand events at the local, regional, national andinternational levels. Historical learning through local history is needed to raise awareness of nationalhistory and prevent students from ignorance of the historical value that surrounds it. Understandingstudents SMA Negeri 65 Jakarta to the local history of DKI Jakarta can be quite understanding.Understanding the learners of local history is inseparable from the role of the facilitator in class to linkthe teaching materials with the local history of DKI Jakarta. Learners are given the task to conductactivities directly in the field, especially in their own environment, to examine the traces of history inorder to collect historical facts. Local history-based learning in SMA 65 besides giving local materialsknowledge about history to learners, also train students to apply character values.